Wordwall Integration in Learning: Is it Effective in Encouraging Student Activity? - Uzdah Fikri Annisa; Wawan Krismanto; Ritha Tuken; Yonathan S. Pasinggi (International Journal of Research in Education, 2025)
Technology has become part of a strategy to improve the quality of learning, including in elementary schools. However, the specific influence on student learning activity still needs to be proven empirically. This study aims to measure the effectiveness of Wordwall integration in learning to encourage increased student learning activity by comparing student learning activities that integrate Wordwall with conventional learning. This study uses a quasi-experimental design in the form of a posttest-only control design. The population in this study were all students of 4th grade SDN 3 Parepare, as many as 108 people, while the sample used was class 4.1 as an experimental class with 37 students and 4.2 as a control class with 36 students. The treatment given to the experimental class was to integrate Wordwall during the learning process from the beginning to the end of learning. The research data were obtained from the posttest of the observation results of learning activity by observers in the experimental and control classes. The data analysis technique was the Independent Sample T-test. The result is that students in classes that integrate Wordwall into their learning have better learning activities. The inferential statistical analysis results showed Sig (2-tailed) = 0.00 <0.05, so H0 was rejected and H1 was accepted. Thus, this study concludes that there is a difference in learning activity between students taught with the integration of Wordwall game media and students taught with conventional media. Wordwall integration into learning can effectively encourage learning activity. Future researchers can examine more in-depth aspects related to the use of Wordwalls in elementary school learning, such as cognitive aspects, challenges and barriers.